2022
DOI: 10.3390/cells11091516
|View full text |Cite
|
Sign up to set email alerts
|

The Role of N6-Methyladenosine in the Promotion of Hepatoblastoma: A Critical Review

Abstract: Hepatoblastoma (HB) is a rare primary malignancy of the developing fetal liver. Its course is profoundly influenced by genetics, in the context of sporadic mutation or genetic syndromes. Conventionally, subtypes of HB are histologically determined based on the tissue type that is recapitulated by the tumor and the direction of its differentiation. This classification is being reevaluated based on advances on molecular pathology. The therapeutic approach comprises surgical intervention, chemotherapy (in a neoad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
(194 reference statements)
0
12
0
Order By: Relevance
“…Recently, Jehan et al identified that TQ selectively promotes HCC apoptosis in synergy with the p53 status, which may harbor relevance for most current tumor RNA modification studies [ 119 , 120 ]. In this study, the cytotoxic effects of TQ, alone or in combination with cisplatin and doxorubicin, were investigated in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jehan et al identified that TQ selectively promotes HCC apoptosis in synergy with the p53 status, which may harbor relevance for most current tumor RNA modification studies [ 119 , 120 ]. In this study, the cytotoxic effects of TQ, alone or in combination with cisplatin and doxorubicin, were investigated in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Weng et al. ( 19 ) have demonstrated that METTL14 and YTHDF1 participate in neurogenesis by promoting protein translation, implying the pivotal role of m 6 A in mRNA translation. All these findings make m 6 A a new target for inhibiting inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Zhang et al (18) has shown that YTHDF1 regulates cell stability by promoting the translation of m 6 A-modified Robo3.1 mRNA. In addition, Weng et al (19) have demonstrated that METTL14 and YTHDF1 participate in neurogenesis by promoting protein translation, implying the pivotal role of m 6 A in mRNA translation. All these findings make m 6 A a new target for inhibiting inflammation.…”
Section: Rna Metabolism Regulated By M 6 a Methylationmentioning
confidence: 99%
“…In addition, metatranscriptomic studies focused on RNA sequencing (RNA seq) also allow functional changes to be discovered to decipher what can affect antibiotic resistance gene expression after exposure to antibiotics. They can also study changes in the virulence factors of specific pathogens and epigenomic studies of some neoplastic conditions ( Sharma et al, 2010 ; Korry et al, 2020 ; Auld et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%